P139 Disease modifying treatment: the end of a golden age. (26th April 2021) - Stanway, James; Walker, David
Abstract: Background/Aims   The role of gold changed from first line DMARD to use in cases where other options were limited, either due to contraindication or ineligibility for biologics. In Autumn 2019, IM gold was withdrawn by the manufacturer due to supply issues, without consultation of the Rheumatology community. As such, a group of patients with difficult to manage disease have lost a key DMARD. We aimed to assess the impact of the withdrawal of gold on the management of IA within Northumbria Healthcare Trust. Methods   Retrospective case note review. Results   We identified 37 patients on gold as of Autumn 2019; 16 for seropositive RA; 4 for PsA; 16 for seronegative RA and 1 for axial spondyloarthritis. 28 were taking gold monotherapy, with 3 receiving regular glucocorticoid in addition. Eight were taking gold in combination with a csDMARD and one in combination with rituximab. Data are currently available for 30 patients regarding the circumstances of gold initiation. Of these, all had received at least one alternative csDMARD which was either inefficacious or intolerable. Reasons for avoiding biologics were not documented in all cases; concerns regarding frequent chest infections were common and documented as a clear contraindication in 5. Follow up has been impacted by COVID-19; only 19 patients have had follow up within the last 6 months, 7 have not been followed up since gold cessation. Fourteen (37.8%) have commenced an alternative DMARD. Six of these have commenced a high cost drug; rituximab (3), adalimumab (2) or tofacitinib (1). Five have commenced hydroxychloroquine (with one subsequently switching to leflunomide), 2 methotrexate and 1 minocycline. Seropositive RA and PsA patients are more likely to have commenced an alternative DMARD, 8/16 and 2/4 respectively; compared to 4/16 with seronegative RA. Of 23 patients who have not commenced alternative DMARDs, 17 have been reviewed following gold cessation; 3 were felt to need additional treatment; 1 has been deferred due to COVID-19 and 2 did not meet criteria for biologic treatment when assessed in early 2020 and subsequent follow up has been delayed. Fourteen patients were felt not to need an additional DMARD, although 1 required an increase in methotrexate and 6 continued co-prescribed DMARDs at the usual dose. Conclusion   The majority of patients have not required additional treatment although for some patients this may reflect the fact that the COVID-19 pandemic has significantly restricted routine follow up. This unusual case of forced DMARD cessation highlights the fact that drug free remission is possible and the ongoing need for immunosuppression should be reviewed. This also raised the ethical question of weather it is right to cease the production of medication which for some patients may be the only effective treatment option. Disclosure   J. Stanway: None. D. Walker: None.